2008
DOI: 10.1681/asn.2007010029
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanisms of Antidiuretic Effect of Oxytocin

Abstract: Oxytocin is known to have an antidiuretic effect, but the mechanisms underlying this effect are not completely understood. We infused oxytocin by osmotic minipump into vasopressin-deficient Brattleboro rats for five days and observed marked antidiuresis, increased urine osmolality, and increased solute-free water reabsorption. Administration of oxytocin also significantly increased the protein levels of aquaporin-2 (AQP2), phosphorylated AQP2 (p-AQP2), and AQP3 in the inner medulla and in the outer medulla plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
68
2
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(78 citation statements)
references
References 18 publications
(34 reference statements)
5
68
2
2
Order By: Relevance
“…AVP increases water permeability along the collecting duct by binding the V2 receptor which, in turn, triggers short-term upregulation of the AQP2 water channel and long-term AQP2 protein transcription. In addition, the role of OXT in inducing SIADH was suggested by two (now dated) reports of water intoxication following OXT infusion (8,9) and by a more recent experimental study (10) that demonstrated that OXT can bind the V2 receptor and stimulate water permeability of the collecting duct and that its effect can be blocked by a V2 receptor inhibitor. However, neither agonists of V2R (AVP and OXT) nor the molecules involved in signal transduction (V2R and AQP2) revealed any genetic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…AVP increases water permeability along the collecting duct by binding the V2 receptor which, in turn, triggers short-term upregulation of the AQP2 water channel and long-term AQP2 protein transcription. In addition, the role of OXT in inducing SIADH was suggested by two (now dated) reports of water intoxication following OXT infusion (8,9) and by a more recent experimental study (10) that demonstrated that OXT can bind the V2 receptor and stimulate water permeability of the collecting duct and that its effect can be blocked by a V2 receptor inhibitor. However, neither agonists of V2R (AVP and OXT) nor the molecules involved in signal transduction (V2R and AQP2) revealed any genetic abnormalities.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally AVP metabolism is significantly changed in pregnancy. All of these lead to in a decrease in serum sodium concentration and serum osmolality by approximately 5 mEq/L and 10 mOsm/kg, respectively [21][22][23]. Although mild hyponatremia is part of the normal physiology of pregnancy, other factors may exacerbate this decline in serum sodium levels such as sodium restriction, polydipsia or inappropriate hypotonic intravenous fluid therapy [11,17].…”
Section: Discussionmentioning
confidence: 99%
“…17 Kidneys were dissected on ice into OMϩC and IM regions. Tissue samples were immediately homogenized in a glass homogenizer at 4°C.…”
Section: Protein Isolationmentioning
confidence: 99%